ICT investment in Spanish SMEs of service and retail sectors. Is it determined by managers gender? - Expósito-García, Alfonso; Sanchis-Llopis, Amparo; Sanchis-Llopis, Juan Alberto (My University, 2023)
This study investigates the role of the entrepreneur’s gender on digitalization strategies undertaken by SMEs in the service and retail sectors. Specifically, we aim at testing how the gender of the entrepreneur may affect investment in software and equipment related to information and communication technologies (ICT). We use a sample of 1,041 Spanish businesses and estimate a bivariate probit model for these two decisions, controlling for other entrepreneurial and business characteristics. Results indicate a higher probability of male entrepreneurs to invest in software and ICT equipment, as compared to women. Furthermore, we find that entrepreneurial risk-taking and business’ innovation capabilities are important drivers for engaging in these two digitalisation strategies, regardless of the gender of the entrepreneur, and that entrepreneurial proactiveness is especially important for women entrepreneurs, since the positive impact of entrepreneurial proactiveness on the probability to engage in digitalisation strategies is stronger in women-led businesses.
Keywords: Ejecutivas; Pequeñas y medianas empresas - Innovaciones tecnológicas; Digitalización; PYMES; Género; España